Lagomorpha as a Model Morphological System - Kraatz, Brian; Belabbas, Rafik; Fostowicz-Frelik, Łucja; Ge, De-Yan; Kuznetsov, Alexander N.; Lang, Madlen M.; López-Torres, Sergi; Mohammadi, Zeinolabedin; Racicot, Rachel A.; Ravosa, Matthew J.; Sharp, Alana C.; Sherratt, Emma; et al. (Frontiers in Ecology and Evolution, 2021)
Due to their global distribution, invasive history, and unique characteristics, European rabbits are recognizable almost anywhere on our planet. Although they are members of a much larger group of living and extinct mammals (Mammalia, Lagomorpha [rabbits, hares, and pikas]), the group is often characterized by several well-known genera (e.g., Oryctolagus, Sylvilagus, Lepus, and Ochotona). This representation does not capture the extraordinary diversity of behavior and form found throughout the order. Model organisms are commonly used as exemplars for biological research, but there are a limited number of model clades or lineages that have been used to study evolutionary morphology in a more explicitly comparative way. We present this review paper to show that lagomorphs are a strong system to study macro- and micro-scale patterns of morphological change within a clade that offers underappreciated levels of diversity. To this end, we offer a summary of the status of relevant aspects of lagomorph biology.